2013
DOI: 10.1248/bpb.b13-00272
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine Potentiates the Hypoglycemic Efficacy of Berberine by Inhibiting P-Glycoprotein Function

Abstract: This study was designed to improve the absorption and hypoglycemic efficacy of berberine (BBR), which is a substrate of P-glycoprotein (P-gp), by combination with a P-gp inhibitor tetrandrine (Tet). Flow cytometry and LC-MS/MS were used to determine the cellular efflux or retention of chemicals. Pharmacokinetic study was performed in ICR mice following oral administration of the study compounds. The hypoglycemic efficacies of the compounds were evaluated in diabetic KK-Ay mice. In the in vitro experiments, Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…This finding could partially explain the pharmacological activities of BBR in various tissues despite its low blood concentration [117, 122]. Our previous work showed that the metabolites of BBR could activate AMPK, as well [123].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could partially explain the pharmacological activities of BBR in various tissues despite its low blood concentration [117, 122]. Our previous work showed that the metabolites of BBR could activate AMPK, as well [123].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to what was mentioned above, recent studies indicated that the anti-inflammatory activity of BBR was also associated with its beneficial effects in the gut [114–116]. Due to the possible low bioavailability [117], high concentration of BBR in the gut after oral administration could modulate the structure of gut microbiota, resulting in the enrichment of short-chain fatty acid (SCFA)-producing bacteria in the gut [114]. SCFA could improve intestinal barrier function and prevent inflammation by blocking exogenous antigen or endotoxin to enter into the blood [118].…”
Section: Discussionmentioning
confidence: 99%
“…Tetrandine P-gp efflux of berberine is inhibited by tetrandine Potentiation of hypoglycemic activity of berberine (Zhang et al, 2014) L-DOPA Berberine leads to degeneration of dopaminergic neuronal Antagonistic action (Shan et al, 2013) cells …”
Section: Activitymentioning
confidence: 99%
“…Both substances interact with P-glycoprotein, and the performance of berberine is affected negatively by P-glycoprotein-mediated intestinal extrusion. P-glycoprotein antagonists, whether synthetic [99] or natural like silymarin [100], improve both berberine bioavailability and efficacy.…”
Section: The Poor Oral Bioavailability Of Herbal Drugsmentioning
confidence: 99%